TEACHING LANGUAGE FORT ADULT LEARNERS: LANGUAGE ANXIETY AND CLASSROOM DYNAMIC - Santi Mayasari (Jurnal Dosen Universitas PGRI Palembang)
AbstrakLanguage is one of media for people to communicate. We can use language to express our feeling, emotion, and ideas by using language. Language can help us facing and solving the problems in our lives, language also can show the character of someone. Up to now, we do not realize that where and when we know language such us uneasiness, frustration, self-doubt, unconfidense, etc. it is called by language anxiety. In other words, language anxiety can be covered by how the teacher and peer students actually react verbally and non-verbally to the efforts an individual makes in order to learn, assimilate knowledge and perform. What and how the situational anxiety which appears only under certain circumstances. In a language classroom, these circumstances include what and how everything happenas in and between the participants in the classroom. There are some reasons why the language anxiety and language dynamic can happen in our cl;assroom, they are: being judged in the classroom, feeling isolated in the classroom, feeling loss of control in the classroom, dose starting late mean “too late”?, a successful learning environment, caring and sharing in the foreign language classroom, clear sense of direction, sense of fun.Key word: Language Teaching, Adult Learner, Language Anxiety, Classroom Dynamic